Was V.I. Grigorovich in Rome? Comprehensive analysis of the notes of V.I. Grigorovich from the archives of the Russian State Library - L.Yu. Aristova; P.V. Georgiev; R.A. Karimova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with the problem of the unknown travel of V.I. Grigorovich abroad and to Rome in 1840–1841. These records contained travel notes, as well as the author’s reflections on the fate of ancient Rome and emotional description of their own feelings and thoughts when visiting certain historical places. One of these places, namely Monte Cavo, near Rome, made a special impression on the author. On the basis of these diary entries, F. Uspensky came to the conclusion that in Rome V.I. Grigorovich allegedly descended something like a revelation from above, a moral fracture occurred, opened a certain truth that influenced all his future activities. Using linguistic analysis, an attempt was made to identify the author of anonymous entries from V.I. Grigorovich’s archive in the Russian State Library. By means of the cognitive analysis, the elements of Slavic narrative were considered in other works by V.I. Grigorovich. The paper presents different views on the authorship of diary entries, including those expressed by N. Bulich and A. Sergeev. On the basis of V.I. Grigorovich’s articles and his “Notebook of Draft Records”, his historical and religious views, as well as his attitude to the idea of pan-Slavism and the historical mission of the Slavs were analyzed.